Performance of procalcitonin in diagnosing parapneumonic pleural effusions: A clinical study and meta-analysis. Issue 33 (August 2017) - He, Chao; Wang, Bo; Li, Danni; Xu, Huan; Shen, Yongchun
Abstract: Background: Parapneumonic pleural effusion (PPE) is a common complication of pneumonia. The accurate diagnosis of PPE remains a challenge. Recent studies suggest that procalcitonin (PCT) emerges as a potential biomarker for PPE. Our study aimed to determine the diagnostic value of PCT for PPE by a clinical study and summarize the overall diagnostic performance of PCT through a meta-analysis. Methods: Demographic and clinical data of the patients with PPE and controls were collected in our clinical study. The diagnostic performances of serum PCT (s-PCT) were analyzed via receiver operating characteristic (ROC) curve analysis, using area under the curve (AUC) as a measure of accuracy. Literature databases were systematically searched for the studies examining the accuracy of PCT for diagnosing PPE. Data on sensitivity, specificity, positive/negative likelihood ratio (PLR/NLR), and diagnostic odds ratio (DOR) were pooled. Summary ROC curves and AUC were used to evaluate overall test performance. Results: In our clinical study, 47 patients with PPE and 101 controls were included. The s-PCT levels were significantly increased in the setting of PPE (5.44 ± 9.82 ng/mL) compared with malignant PE (0.15 ± 0.19 ng/mL), tuberculous PE (0.18 ± 0.16 ng/mL), and transudates (0.09 ± 0.03 ng/mL) ( P  < .001). Using a cutoff value of 0.195 ng/mL, the sensitivity and specificity of s-PCT in diagnosing PPE were 0.83 and 0.80, respectively, and AUC was 0.89. In addition, 11 studies were included in our meta-analysis. Summary performance estimates for s-PCT in diagnosing PPE were as follows: sensitivity, 0.78 (95% CI: 0.71–0.84); specificity, 0.74 (95% CI: 0.69–0.78); PLR, 3.46 (95% CI: 2.09–5.74); NLR, 0.27 (95% CI: 0.14–0.54); DOR, 12.37 (95% CI: 4.34–41.17); and AUC, 0.84. The corresponding estimates for p-PCT were as follows: sensitivity, 0.62 (95% CI: 0.57–0.67); specificity, 0.71 (95% CI: 0.68–0.75); PLR 2.31 (95% CI: 1.81–2.95); NLR, 0.47 (95% CI: 0.35–0.63); DOR, 5.48 (95% CI: 3.07–9.77); and AUC, 0.80. Conclusion: Both s-PCT and p-PCT might have modest performance in diagnosing PPE. However, more studies on a large scale should be performed to confirm our findings.